The printed square vintage handkerchief patterns for fashion and design - Albrechtsen, Nicky (London Thames & Hudson, 2012)
Suitable for collectors of printed textiles, fashion lovers and designers, this title features over 200 designed handkerchiefs that have been selected to reflect the magnificent array of printed designs that emerged between the 1920s and 1950s.
Red -- Orange -- Yellow -- Green -- Azure -- Blue -- Pink -- Purple -- Beige -- Brown -- Black and White.
Includes bibliographical references (p. 254).
Keywords: Handkerchiefs -- History -- 20th century; Handkerchiefs -- Design